Psychoeducation of Stunting Prevention Through Good Parenting for Parents Who Have Children Under Five - Tasya Fallerina Putri; Febrina Amelia Putri; Dewi Anjani; Salsabilah Fahira Putri; Amalia Juniarly (Universitas Muhammadiyah Palembang, 2023)
Stunting is a condition where toddlers experience a lack of nutritional intake for a long period of time so that children experience growth disorders, namely their height is shorter than the standard age. One of the factors for children experiencing stunting is parenting from parents so that every parent needs to have knowledge about how to care for children properly. This activity was carried out using the lecture/counseling method and distributing leaflets. Based on the results of the pre-test and post-test, there was an increase in the knowledge of all participants by 75,1%. The psychoeducation carried out was quite successful in increasing parents' knowledge and awareness about the importance of good parenting for toddlers as an effort to prevent stunting. In order for the psychoeducation process to run continuously, there needs to be further monitoring of the community by the community health center.